ADAT PERNIKAHAN SUKU BANJAR DAN SUKU BUGIS - M. Ahim Sulthan Nuruddaroini (Lembaga penelitian dan pengabdian kepada Masyarakat, 2019)
Culture and society are one unity that cannot be separated from each other, therefore with the existence of various ethnic groups, various traditions are born. In addition, culture can be seen as values that are believed to be shared in a society and can be internalized in individuals so that they live in every behavior, one of which is in the marriage customs of each tribe that has unique and very interesting differences and we must know and preserve, because Indonesia is very rich in culture that we must guard together, by knowing the difference does not mean we insult and blame instead guard and respect each other. The purpose of this study was to determine the differences and similarities of the marriage customs of the Banjar and Bugis tribes. The method that I use is a qualitative method. Type of library research (library reseach), the approach used is an ethnographic approach by examining cultural phenomena that exist in society. The results of this study are the marriage customs of the Banjar and Bugis tribes that have differences and similarities. The first difference is about the term money given to women from the male side by the term uag jujuran (Banjar tribe) and panai money (Bugis tribe), while the equation is something that must be fulfilled in the custom of marriage and the same form money. The next difference is about the factors that influence the high and low amount of money given, then in practice it also has similar differences and similarities, only procedurally different.